Iron Disulfide (FeS2): A Promising Material for Removal of Industrial Pollutants. Issue 6 (27th February 2017) - Kaur, Gurpreet; Singh, Bikramjeet; Singh, Paviter; Singh, Kulwinder; Thakur, Anup; Kumar, Manjeet; Bala, Rajni; Kumar, Akshay
Abstract: For environmental concerns, there is need of cost effective method for the removal of toxic and carcinogenic dyes used in industries that pose a serious threat to humankind as well as marine life/ecosystems. FeS2 is a promising semiconductor photocatalyst because of its high potential to degrade dyes as well as organic materials. In the present study, FeS2 was successfully synthesized using low cost and more effective hydrothermal method. The different features of synthesized FeS2 material was confirmed by X‐ray diffraction, transmission electron microscopy, UV‐visible spectrophotometry. Methyl orange dye and also a textile dye that contribute as a major organic pollutant was effectively degraded by photo catalytically active FeS2 nanostructures. The maximum degradation efficiency (93.09%) was occurred in 120 minutes with 1 g/L FeS2 catalyst dose. The dye removal efficiency for a textile dye Novacron yellow Huntsman (NYH) approximately 98.15 % was achieved with 1 g/L FeS2 catalyst in just 80 min irradiation of visible light. This work further insights to develop FeS2 nanostructures photocatalyst for the removal of toxic and hazardous water contaminants. Abstract : The as synthesized FeS2 nanostructures were well degrade methyl orange dye with degradation efficiency of 93.09% in 120 minutes with 1g/L catalyst dose. The degradation efficiency of about 98.15% was achieved with 1g/L FeS2 with textile dye Novacron yellow Huntsman (NYH) in small period of time i.e. 80 minutes. Thus, FeS2 is a potentially attractive visible light driven photocatalyst for removal of industrial pollutants.